A new tool to assess understanding of Down syndrome screening information presented by midwives. (2nd November 2019) - John, Sophie; Kirk, Maggie; Tonkin, Emma; Stuart-Hamilton, Ian
Abstract : Aim: To identify factors that could influence women's understanding of Down syndrome (DS) screening information presented by midwives. Methods: Current literature was scrutinised. Components that could influence women's understanding were identified and a new framework was developed and refined. Measures were selected and developed to create a tool to assess the framework. Findings: A new framework and assessment tool, measuring understanding of screening information and communication (MUSIC), was developed to assess women's understanding of DS screening information, their cognitive status and the midwives' communicative style. Conclusion: This framework is the first of its kind, encompassing both women's cognitive status and midwife communication as an influence on women's understanding. Applying the framework and tool could inform midwifery practice by providing an insight into whether, to what extent and how, cognitive status influences understanding of DS screening information, the importance of tailoring information to each woman and highlighting areas of communication that are most effective.